Outcome of Patients With Esophageal Atresia and Very Low Birth Weight (≤ 1,500 g) - Ritz, Laura Antonia; Widenmann-Grolig, Anke; Jechalke, Stefan; Bergmann, Sandra; von Schweinitz, Dietrich; Lurz, Eberhard; Hubertus, Jochen (Frontiers in Pediatrics, 2020)
Introduction: Primary repair of esophageal atresia (EA) in infants with very low birth weight (VLBW) and extremely low birth weight (ELBW) has been widely performed in pediatric surgery. However, several studies have shown that complication rates in infants with VLBW are high. We hypothesize preterm children benefit from a shorter, less-traumatizing operation in the first days of life, as staged repair implies. Methods: Patients with EA and VLBW were retrieved from the database of a large national patient organization KEKS e.V. Structured questionnaires were sent to all the patients’ families; the responses were pseudonymized and sent to our institution. Results: Forty-eight questionnaires from patients were analyzed. The mean birth weight was 1,223 g (720–1,500 g). Primary repair was performed in 25 patients (52%). Anastomotic insufficiency (AI) was reported in 9 patients (19%), recurrent fistula (RF) in 8 (17%), and anastomotic stenosis in 24 patients (50%). Although AI was almost twice as common after primary repair than after staged repair (24% versus 13%; p = 0.5), the difference was not statistically significant. RF was more frequent after primary repair (28% versus 4%; p = 0.04), gastroesophageal reflux was more frequent in the group after staged repair (78% versus 52%; p = 0.04), and both correlations were statistically significant. Intracranial hemorrhage (ICH) was reported in 11 patients (23%) and was observed in 7 of them (64%, p = 0.4) after primary repair. ICH was reported in 60% of patients with ELBW and 75% of patients when ELBW was paired with primary repair. Conclusion: This study demonstrates the complication rate in patients with VLBW is higher than the average of that in patients with EA. The study indicates that a staged approach may be an option in this specific patient group, as less RF and AI are seen after staged repair. ICH rate in patients with ELBW seemed to be especially lower after staged repair. Interestingly, gastroesophageal reflux was statistically significantly higher in the group after staged repair, and postoperative ventilation time was longer. It is, therefore, necessary to individually consider which surgical approach is appropriate for this special patient group.